Comparison of Frozen and Final Pathology Results in Patients Operated for Endometrial Hyperplasia - Turker Ergun, Gonca; Zorlu, Ugurcan; Elmas, Burak; Baris Akcan, Bengü Nur; Kurtaran, Gul; Cetinkaya, Kadir; Doganay, Melike (Gynecology Obstetrics & Reproductive Medicine, 2024)
OBJECTIVE: Our study aimed to determine the frequency of endometrial cancer in patients undergoing surgery with a diagnosis of endometrial hyperplasia and to evaluate the concordance between preoperative diagnosis, frozen section examination, and final pathology results. STUDY DESIGN: The clinical findings, imaging results, and all pathology reports of patients who underwent total abdominal hysterectomy for endometrial hyperplasia (atypical or non-atypical) between January 2020 and January 2023 at our hospital were retrospectively evaluated. Demographic and clinical characteristics (age, menopausal status, parity, body mass index, presence of diabetes and hypertension) and pathology results were recorded from patient records. RESULTS: 144 patients diagnosed with endometrial hyperplasia were included in the study. The frozen section and final pathology results of all patients diagnosed with non-atypical endometrial hyperplasia were reported as benign lesions. In the atypia group, the intraoperative frozen section results of 80.7% of the patients were classified as benign lesions, while the results of 19.3% were reported as malignant pathology. A statistically significant difference was found between the benign and malignant lesion groups, which were classified based on the final pathology results, with respect to age, menopausal status, and average endometrial thickness before biopsy. CONCLUSION: In cases of endometrial hyperplasia with atypia, the possibility of cancer appearing in the final pathology results should be taken into consideration. In the preoperative evaluation of patients, characteristics such as endometrial thickness, age, and menopausal status may suggest the likelihood of encountering endometrial cancer during surgery in this patient group.